2022
DOI: 10.1039/d2ta02234f
|View full text |Cite
|
Sign up to set email alerts
|

Atomically miniaturized bi-phase IrOx/Ir catalysts loaded on N-doped carbon nanotubes for high-performance Li–CO2 batteries

Abstract: Li-CO2 batteries are bifunctional, spontaneously storing energy and fixing environmental CO2 without external electricity. Identifying efficient catalysts that can accelerate the reversible formation and decomposition of the insulating carbonate products...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 76 publications
2
12
0
Order By: Relevance
“…The relatively high nucleation overpotential are mainly correlated with the low loading of SnCu 1.5 O 3.5 clusters and inferior conductivity of the MFI zeolites support. [ 45–48 ] In this study, the actual contents of Sn and Cu in the SnCu 1.5 O 3.5 @MFI composites were estimated to be 0.225 and 0.198 wt% with ICP‐MS method, respectively (Table S1, Supporting Information). Nevertheless, the SnCu 1.5 O 3.5 @MFI catalyst presents an impressive bifunctional catalytic activity for the formation and decomposition of Li 2 CO 3 /C for Li‐CO 2 batteries in a wide current density range.…”
Section: Resultsmentioning
confidence: 95%
“…The relatively high nucleation overpotential are mainly correlated with the low loading of SnCu 1.5 O 3.5 clusters and inferior conductivity of the MFI zeolites support. [ 45–48 ] In this study, the actual contents of Sn and Cu in the SnCu 1.5 O 3.5 @MFI composites were estimated to be 0.225 and 0.198 wt% with ICP‐MS method, respectively (Table S1, Supporting Information). Nevertheless, the SnCu 1.5 O 3.5 @MFI catalyst presents an impressive bifunctional catalytic activity for the formation and decomposition of Li 2 CO 3 /C for Li‐CO 2 batteries in a wide current density range.…”
Section: Resultsmentioning
confidence: 95%
“…(F) Performance comparisons with reported carbon and noble metal‐based (Ru, Rh, Ir, etc.) cathode catalysts for Li–CO 2 batteries 1,2,6,10,12–14,30–71 (the number on the top of each cylinder means various cathode catalysts, and the corresponding cathode catalysts from 1 to 49 are listed in Table S1 in detail).…”
Section: Resultsmentioning
confidence: 99%
“…Further efforts were devoted to investigating the catalytic activity of Ru SACs in LCBs, and these studies also confirmed the superior battery performance of SACs compared with that of nanoparticles. 50,191 In 2022, Ryu et al 192 atomically dispersed IrO x /Ir bi-phase particles as SACs on nitrogen-doped carbon nanotubes (NCNTs) to accelerate the reversible formation and decomposition of the insulating carbonate products formed on the electrode of LCBs. Herein, to prove its effectiveness, researchers controlled the particle size and loading of Ir catalysts on the NCNTs (denoted as s-Ir/NCNTs, m-Ir/NCNTs, and l-Ir/NCNTs, with average particle sizes of 0.42, 1.75 and 2.69 nm, respectively).…”
Section: Noble Metal Sacsmentioning
confidence: 99%